1984
DOI: 10.1111/j.1532-5415.1984.tb04177.x
|View full text |Cite
|
Sign up to set email alerts
|

The Attitudinal Impact of Training in Gerontology/Geriatrics in Medical School: A Review of the Literature and Perspective

Abstract: The authors review the literature regarding the effect of education on medical student attitudes toward patient care and toward geriatric patient care in particular. The ability of gerontologic/geriatric programs to foster positive attitudes toward the elderly has been modest. Empathically oriented programs that stress the establishment of contact with healthy, functioning older persons, however, may be twice as effective as cognitively oriented programs that stress the acquisition of technical knowledge. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
4

Year Published

1986
1986
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 40 publications
2
29
0
4
Order By: Relevance
“…The review has the advantage of using a systematic rather than a narrative approach and constructed eligibility criteria that incorporated studies with a clear design and objective educational outcome based on the BEME hierarchy. 14 In keeping with previous reviews of the effect of teaching interventions aiming to improve student attitudes, 45 interventions analyzed in this review that focused on evaluation of attitudes showed a mixed picture, although there appeared to be a trend for interventions of longer duration (years rather than hours or days) to be more likely to improve attitudes than briefer interventions. This finding has implications for the delivery of geriatrics teaching in medical schools; although shorter, more-intensive teaching sessions may be cheaper and easier to deliver within a curriculum, the evaluation of longer-term curricular changes should be considered when aiming to improve attitudes toward older adults.…”
Section: Discussionmentioning
confidence: 74%
“…The review has the advantage of using a systematic rather than a narrative approach and constructed eligibility criteria that incorporated studies with a clear design and objective educational outcome based on the BEME hierarchy. 14 In keeping with previous reviews of the effect of teaching interventions aiming to improve student attitudes, 45 interventions analyzed in this review that focused on evaluation of attitudes showed a mixed picture, although there appeared to be a trend for interventions of longer duration (years rather than hours or days) to be more likely to improve attitudes than briefer interventions. This finding has implications for the delivery of geriatrics teaching in medical schools; although shorter, more-intensive teaching sessions may be cheaper and easier to deliver within a curriculum, the evaluation of longer-term curricular changes should be considered when aiming to improve attitudes toward older adults.…”
Section: Discussionmentioning
confidence: 74%
“…3 Beginning medical students have already formed some unfavorable attitudes about older people. [4][5][6][7][8] Pretests typically show little knowledge of the aging process, negative stereotypes of older people, and preference to care for younger patients. 9 There is evidence to support the efficacy of a concentrated geriatrics block 10 and of the benefits of exposing medical students to the geriatric population early in their undergraduate medical education.…”
mentioning
confidence: 99%
“…Although Thailand's growth rate of its aging population is three times faster than that of the developed countries, there is no data surveying the attitude of both MS and MR trainees toward geriatric medicine that would help steer the direction of curricular development (''World population prospects: The 2006 revision population database, '' 2007). Previous studies suggested that most medical students have little knowledge about aging, have mixed attitudes about the elderly and their care, and have low interest in pursuing geriatric medicine as a career (Chiang, 1998;Coccaro & Miles, 1984). Additionally, one study showed that only 4% of doctors who chose geriatric medicine as a career in the United Kingdom made their career choice while they were medical students (Briggs, Atkins, Playfer, & Corrado, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Care for the elderly requires specific knowledge, attitudes, and skills that expand across the continuum of medical education from medical school through postgraduate training. Previous studies showed that medical students have mixed attitude towards the elderly and their care and low interest to pursue a career in geriatric medicine (Chiang, 1998;Coccaro & Miles, 1984). Additionally, there was a study that reported an association between students' positive attitudes about the elderly and their care and an increased interest in geriatric medicine (Fitzgerald, Wray, Halter, Willians, & Supiano, 2003).…”
mentioning
confidence: 94%